Motivational Teaching Speaking Strategy to Achieve Goal Orientation of Language Learner - Hamim, Miftahul (Journal of English Teaching, Literature, and Applied Linguistics, 2018)
One of the most important skills in EFL is speaking skill. It employs the best influence when seeing goal of speaking learning process. This matter has become essential for teacher as the facilitator and director of the language teaching and learning to formulate certain strategy in improving learner’ motivation to achieve their goal orientation. This article investigated the motivational strategy in teaching speaking Class achievement to achieve students’ goal orientation. Goal orientation has emerged as an important motivational construct in organizational research providing an explanation for that individuals use to engage in achievement activities. The lack of confidence on the students might appear as one of factors that lead the learners into their less mastery on speaking. The use of motivational strategies on speaking class to promote student’s achievement on goal orientation on speaking can be inferred by encouraging mastery oriented learning and promoting performance oriented learning. Those two motivational strategy in speaking will drive the students on their goal orientation in which this is divided into mastery and performance oriented learning that drive learner into their motivated mind which leads them into their reachable goal.